2015
DOI: 10.1016/j.critrevonc.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Papillary renal cell carcinoma: A review of the current therapeutic landscape

Abstract: Renal cell carcinoma (RCC) is the most common cancer of the kidney and accounts for 2-3% of all adult malignancies. Clear cell carcinoma represents the most common histologic subtype, while papillary Renal Cell Carcinoma (pRCC) accounts for 10-20% of all renal cell cancers. While the inactivation of VHL gene can be found in the majority of clear cell carcinomas, different molecular mechanisms are involved into pRCC biology. Mutations in the MET oncogene are an essential step into the pathogenesis of hereditary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 86 publications
2
133
0
3
Order By: Relevance
“…Subgroup data from clinical trials in non-clear cell RCC (non-ccRCC) patients have demonstrated modest clinical efficacy associated with inhibition of VEGF and mTOR pathways in pRCC, and the prognosis of these patients remains poor [24]. Several strategies targeting the MET pathway in metastatic pRCC are being explored [25].…”
Section: Management Of Metastatic Renal Cancermentioning
confidence: 99%
“…Subgroup data from clinical trials in non-clear cell RCC (non-ccRCC) patients have demonstrated modest clinical efficacy associated with inhibition of VEGF and mTOR pathways in pRCC, and the prognosis of these patients remains poor [24]. Several strategies targeting the MET pathway in metastatic pRCC are being explored [25].…”
Section: Management Of Metastatic Renal Cancermentioning
confidence: 99%
“…На II стадии клинических испытаний находятся таргетные препараты -синтетические инги-биторы МЕТ форетиниб (XL880), тивантиниб (ARQ197), волитиниб (HMPL-504); рилотумумаб (AMG-102) -моноклональное антитело к HGF (рецептору, кодиру-емому геном МЕТ). Возможно, отдельные испытания в отношении НСРП будут проведены для кабозанти-ниба (XL184) и ингибитора ALK/MET/ROS/RET кри-зотиниба [29,30]. Исследуют также возможности таргет-ной терапии папиллярного РП ингибиторами VEGFR2 (сунитинибом, сорафенибом), ингибиторами mTOR (темсиролимусом, эверолимусом), а также комбиниро-ванного назначения ингибиторов МЕТ с ингибитора-ми EGFR [31].…”
unclassified
“…Исследуют также возможности таргет-ной терапии папиллярного РП ингибиторами VEGFR2 (сунитинибом, сорафенибом), ингибиторами mTOR (темсиролимусом, эверолимусом), а также комбиниро-ванного назначения ингибиторов МЕТ с ингибитора-ми EGFR [31]. Полученные ранее методами классиче-ской цитогенетики данные об увеличении количества копий хромосом 7, 17 и амплификации гена МЕТ, как оказалось, относятся в основном к папиллярному РП I типа, тогда как для II типа более характерна утра-та хромосом 8, 11, 18, что было показано методом срав-нительной геномной гибридизации [30,32].…”
unclassified
“…1,2,10 In recent years, the treatment of ccRCC has undergone dramatic changes with the development of FDA-approved targeted therapies including mTOR inhibitors and tyrosine kinase inhibitors of VEGF and its relatives. [11][12][13] However, there are few published clinical trials specifically evaluating the effects of these compounds in pRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Second in frequency to clear cell renal cell carcinoma (ccRCC) which accounts for approximately 70-80% of cases, pRCC represents up to 10-20% of all RCCs. 1,2 Histologically, pRCC is characterized by a predominantly papillary growth pattern with tubular areas and fibrovascular cores. 3 Genetically, pRCC is marked by high incidence of trisomy or tetrasomy of chromosome 7, where genes for the MET receptor and its ligand, hepatocyte growth factor (HGF), reside.…”
Section: Introductionmentioning
confidence: 99%